Mega-dogs of New Kansas - Jolley, Dan; Khouri, Jacques (Minneapolis : Graphic Universe, 2020)
"When an official threatens the mega-dog program, Sienna Barlow sneaks away with her dog, Gus, and begins an adventure across New Kansas."--
Ages 7-11
Grades 4-6
Accelerated Reader
jb
Keywords: Girls -- Comic books, strips, etc; Dogs -- Comic books, strips, etc; Human-animal relationships -- Comic books, strips, etc; Survival -- Comic books, strips, etc; Imaginary places -- Comic books, strips, etc